2015
DOI: 10.1080/21642583.2015.1013644
|View full text |Cite
|
Sign up to set email alerts
|

Interval Type-2 fuzzy logic controller design for the speed control of DC motors

Abstract: In this paper, an optimal interval Type-2 Fuzzy controller is designed for the speed control of DC motors. In this way, first, the importance and position of Type-2 fuzzy systems are mentioned. In addition, some properties of Type-2 operators are investigated as well as the properties of membership degree of Type-2 fuzzy sets. A comparison between different parts of Type-1 and Type-2 fuzzy systems, such as fuzzifier, fuzzy inference engine, rule-base and defuzzifier is given. Finally, an Interval type-2 Fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…For example in [28] and [29], non-singleton type-2 FLSs are shown to effectively handle different levels of uncertainties in industrial use cases. It has also been shown that in the presence of perturbations, the generalized type-2 fuzzy controllers outperform their type-1 and interval type-2 counterparts [30], [31], and that interval type-2 NSFLSs outperform type-1 NSFLSs in different application domains [32], [33]. Incorporating other AI techniques with type-2 FLSs has also resulted in hybrid solutions for predicting the behaviour of non-linear complex systems (e.g., using neural networks in [34] and genetic algorithms in [35]).…”
Section: Other Related Workmentioning
confidence: 99%
“…For example in [28] and [29], non-singleton type-2 FLSs are shown to effectively handle different levels of uncertainties in industrial use cases. It has also been shown that in the presence of perturbations, the generalized type-2 fuzzy controllers outperform their type-1 and interval type-2 counterparts [30], [31], and that interval type-2 NSFLSs outperform type-1 NSFLSs in different application domains [32], [33]. Incorporating other AI techniques with type-2 FLSs has also resulted in hybrid solutions for predicting the behaviour of non-linear complex systems (e.g., using neural networks in [34] and genetic algorithms in [35]).…”
Section: Other Related Workmentioning
confidence: 99%
“…Membership functions are classified as type-1 and type-2, because defuzzification process is performed with membership functions and they differ structurally from each other. One of the most important features that separates T2FLC from T1FLC is the type reduction process [12][13][14][15][24][25]. Type-1 and type-2 triangular membership functions are also shown in Fig.…”
Section: Structure Of T2flcmentioning
confidence: 99%
“…The inference mechanism is a simulation of the human decision making process. Typereduction can be expressed as the process of finding the center of gravity of the output membership functions created for the system to be controlled [24][25].…”
Section: Structure Of T2flcmentioning
confidence: 99%
“…The system structure of the QES is built entirely using a fuzzy logic interface system, which has been extensively used in a wide range of problem domains over the past decades [33–38]. This was done because QES uses linguistic terms instead of precise numerical values to describe system behaviour.…”
Section: Quality Evaluation Systemmentioning
confidence: 99%